LEGAL ANALYSIS OF THE TRANSFER OF FUNCTION OF TRADITIONAL LAND INTO OIL PALM PLANTATIONS PERSPECTIVE OF THE MURSALAH PROBLEM - Nasution, Miswar; Tarigan, Tetty Marlina (Pena Cendekia Insani, 2025)
Customary land is land controlled by certain customary communities in areas spread throughout Indonesia. Customary land law is independent because the existing legal norms are living norms that are followed by sanctions and obeyed by the community and the relevant institutions. In the transfer of the function of customary land by the private sector to customary land, it certainly gives a negative response from the community. Maslahah mursalah becomes a source of law where the taking of the land is detrimental to the community, because all sources of life from customary land have provided prosperity, especially if the private sector builds oil palm plantations, the community loses the land that supports various lives. This study uses a normative type taken from library materials.